Silencing Alpha Synuclein in Mature Nigral Neurons Results in Rapid Neuroinflammation and Subsequent Toxicity - Benskey, Matthew J.; Sellnow, Rhyomi C.; Sandoval, Ivette M.; Sortwell, Caryl E.; Lipton, Jack W.; Manfredsson, Fredric P. (Frontiers in Molecular Neuroscience, 2018)
Human studies and preclinical models of Parkinson’s disease implicate the involvement of both the innate and adaptive immune systems in disease progression. Further, pro-inflammatory markers are highly enriched near neurons containing pathological forms of alpha synuclein (-syn), and -syn overexpression recapitulates neuroinflammatory changes in models of Parkinson’s disease. These data suggest that -syn may initiate a pathological inflammatory response, however the mechanism by which -syn initiates neuroinflammation is poorly understood. Silencing endogenous -syn results in a similar pattern of nigral degeneration observed following -syn overexpression. Here we aimed to test the hypothesis that loss of -syn function within nigrostriatal neurons results in neuronal dysfunction, which subsequently stimulates neuroinflammation. Adeno-associated virus (AAV) expressing an shRNA targeting endogenous -syn was unilaterally injected into the substantia nigra pars compacta (SNc) of adult rats, after which nigrostriatal pathology and indices of neuroinflammation were examined at 7, 10, 14 and 21 days post-surgery. Removing endogenous -syn from nigrostriatal neurons resulted in a rapid up-regulation of the major histocompatibility complex class 1 (MHC-1) within transduced nigral neurons. Nigral MHC-1 expression occurred prior to any overt cell death and coincided with the recruitment of reactive microglia and T-cells to affected neurons. Following the induction of neuroinflammation, -syn knockdown resulted in a 50% loss of nigrostriatal neurons in the SNc and a corresponding loss of nigrostriatal terminals and dopamine concentrations within the striatum. Expression of a control shRNA did not elicit any pathological changes. Silencing -syn within glutamatergic neurons of the cerebellum did not elicit inflammation or cell death, suggesting that toxicity initiated by -syn silencing is specific to dopamine neurons. These data provide evidence that loss of -syn function within nigrostriatal neurons initiates a neuronal-mediated neuroinflammatory cascade, involving both the innate and adaptive immune systems, which ultimately results in the death of affected neurons.